(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
Currently, Brazil is among the countries with the most flawed income distribution in the world, despite the progress made throughout the last decade. In an attempt to correct some flaws in the governmental system, some social actors come into play in order to change this reality, they are so called entrepreneurs. Taking in account the previously exposed scenario, this study was developed to analyze the intersection link between entrepreneurship and marketing in the segment of bars in the city of Belo Horizonte, Brazil´s third largest city. Nowadays, the segment of Brazilian bars, which is responsible for over 23% of all enterprises in the country, is marked by a high level of competition and dynamism. In this environment, this study has the general objective to identify the main challenges of bars branches of the entrepreneurial city of Belo Horizonte. To meet this end, a descriptive qualitative study was conducted, with twelve entrepreneurs from the segment of bars in the city of Belo Horizonte / MG, Brazil. All data analysis was based on thematic content analysis, in the light of the propositions of Bardin (2006). Among the results achieved we highlight that the greatest challenges to entrepreneurs are related to lack of strategic planning and poor marketing structure. It is worth saying that most of the analyzed entrepreneurs were classified as entrepreneurs by necessity.